An epidemiologic evaluation of risk factors associated with asthma severity and phenotypes - Busacker, Ashley A., author; Keefe, Thomas J., advisor (Colorado State University. Libraries, 2008)
Asthma is an inflammatory disorder of the airways characterized by airway hyperresponsiveness, periodic episodes of bronchoconstriction and airway obstruction. Severe asthma accounts for a minority of asthma, but utilizes a disproportionate amount of asthma-associated healthcare costs. Further studies are needed to identify risk factors associated with severe asthma, a very heterogeneous disease. Asthma-particularly severe asthma-consists of several different phenotypes. Limited epidemiologic studies have been conducted to identify risk factors specific to severe asthma. Factors associated with proposed asthma phenotypes have not been evaluated in a multivariate manner. This study investigated the risk factors associated with severe asthma, with specific phenotypes of asthma, and the association between a potential biomarker, C-reactive protein (CRP), and aspirin intolerant asthma. The project utilized data that were collected from National Institutes of Health funded studies and data collected from an electronic chart review. Data from questionnaires, histological, radiological and physiological studies were used to determine univariate associations between these factors and asthma severity and then to determine associations between the factors and different asthma phenotypes. Multiple logistic regression analysis was used to evaluate the differences between severe and non-severe asthma, early and late onset asthma, asthma subjects who did or did not exhibit air trapping, and aspirin intolerant and tolerant asthma with particular attention to CRP levels. This investigation found important clinical differences between severe and non-severe asthma that should be further evaluated as risk factors that may give insight into severe-asthma mechanisms to be targeted in asthma treatment. The analysis of asthma phenotypes also yielded important findings. Specifically, early onset asthmatics appear to be a relatively homogeneous group with strong genetic influences and presence of allergic responses, whereas late onset disease is more heterogeneous. The analysis of the air trapping phenotype demonstrated that quantitative CT-determined air trapping in asthmatic subjects identifies a group of individuals with a increased odds of intensive health care utilization. Additionally, several independent risk factors for the presence of this phenotype were identified, perhaps most interestingly history of pneumonia, neutrophilic inflammation, and atopy. Lastly, this study provides evidence that CRP may be elevated in aspirin intolerant subjects and that CRP deserves further study as a potential biomarker for the aspirin intolerant phenotype of asthma.
Keywords: asthma; phenotypes; risk factors; epidemiology